A method to control phosphoinositides and to analyze PTEN function in living cells using voltage sensitive phosphatases - Mavrantoni, Angeliki; Thallmair, Veronika; Leitner, Michael G.; Schreiber, Daniela N.; Oliver, Dominik; Halaszovich, Christian R. (Frontiers in Pharmacology, 2015)
Voltage sensitive phosphatases (VSPs), including engineered voltage sensitive PTEN, are excellent tools to rapidly and reversibly alter the phosphoinositide (PI) content of the plasma membrane in vivo and study the tumor suppressor PTEN. However, widespread adoption of these tools is hampered by the requirement for electrophysiological instrumentation to control the activity of VSPs. Additionally, monitoring and quantifying the PI changes in living cells requires sophisticated microscopy equipment and image analysis. Here we present methods that bypass these obstacles. First, we explore technically simple means for activation of VSPs via extracellularly applied agents or light. Secondly, we characterize methods to monitor PI(4,5)P2 and PI(3,4,5)P3 levels using fluorescence microscopy or photometry in conjunction with translocation or FRET based PI probes, respectively. We then demonstrate the application of these techniques by characterizing the effect of known PTEN mutations on its enzymatic activity, analyzing the effect of PTEN inhibitors, and detecting in real time rapid inhibition of protein kinase B following depletion of PI(3,4,5)P3. Thus, we established an approach that does not only allow for rapidly manipulating and monitoring PI(4,5)P2 and PI(3,4,5)P3 levels in a population of cells, but also facilitates the study of PTEN mutants and pharmacological targeting in mammalian cells.